The role of psychotherapy in chronic pain management - Olga Wysokińska; Anna Małek; Karolina Zadrożna; Klara Iwaniszyn-Zapołoch; Krystian Cholewa (Kazimierz Wielki University, 2022)
Introduction As chronic pain occurs in about 20% of the population, pain management is becoming a more and more crucial branch of medicine and its importance in many fields of medicine increases and is more appreciated. Pain is not only a physical experience, but also has a sensory and emotional component so the modern approach to pain treatment should not be limited to pharmacological treatment alone, but also should provide appropriate multifaceted psychological support to the patient and his relatives. State of knowledge Pathophysiological mechanisms of developing pain can not be unmentioned while analyzing the pain management and effectiveness of psychotherapy , because physiological and psychological aspects of the human body's functioning are inextricably connected. Knowledge of pain assessment methods is always crucial to lead the psychotherapy in a proper and effective way. The mainstay of pain management is pharmacotherapy, using drug groups such as opioids and non-opioid analgesics , but the role of psychotherapy is also very important and there is much research, which proves it. Summary Multidisciplinary treatment of patients with chronic pain is widely recommended, as well as paying attention not only to the somatic aspect, but also to the need for psychological management of these patients. It plays an extremely important role in palliative medicine and the treatment of cancer patients, as well as in neuropathic pain and neurological diseases